Novel Light Source Integration Approaches for Silicon Photonics. Issue 4 (7th July 2017) - Wang, Zhechao; Abbasi, Amin; Dave, Utsav; De Groote, Andreas; Kumari, Sulakshna; Kunert, Bernadette; Merckling, Clement; Pantouvaki, Marianna; Shi, Yuting; Tian, Bin; Van Gasse, Kasper; Verbist, Jochem; et al.
Abstract : This article reviews the most recent progress of the field of silicon integrated light sources. Novel integration approaches of III‐V‐to‐silicon bonding, transfer printing, epitaxial growth and the use of colloidal quantum dots are discussed and recent representative demonstrations are presented. The challenges and perspectives of these approaches are also discussed. Abstract : Silicon does not emit light efficiently, therefore the integration of other light‐emitting materials is highly demanded for silicon photonic integrated circuits. A number of integration approaches have been extensively explored in the past decade. Here, the most recent progress in this field is reviewed, covering the integration approaches of III‐V‐to‐silicon bonding, transfer printing, epitaxial growth and the use of colloidal quantum dots. The basic approaches to create waveguide‐coupled on‐chip light sources for different application scenarios are discussed, both for silicon and silicon nitride based waveguides. A selection of recent representative device demonstrations is presented, including high speed DFB lasers, ultra‐dense comb lasers, short (850nm) and long (2.3μm) wavelength lasers, wide‐band LEDs, monolithic O‐band lasers and micro‐disk lasers operating in the visible. The challenges and opportunities of these approaches are discussed.